Acupuncture Can Regulate the Distribution of Lymphocyte Subsets and the Levels of Inflammatory Cytokines in Patients With Mild to Moderate Vascular Dementia - Zhi, Hui; Wang, Yao; Chang, Shichen; Pan, Pan; Ling, Zhenzhen; Zhang, Zhen; Ma, Zhinan; Wang, Runmin; Zhang, Xuezhu (Frontiers in Aging Neuroscience, 2021)
Background: Vascular dementia (VD) is the second most common type of dementia after Alzheimer's disease, but there is lack of definitive treatment for VD. Acupuncture treatment is effective in improving the cognitive impairment and behavioral capacity of VD patients. However, there are few researches about the acupuncture and the abnormal peripheral immune function of VD. And few studies concern the regulating effect of acupuncture on peripheral immunity of VD patients. Objective: The aim of this study is to explore the effect of “sanjiao” acupuncture method on peripheral immunity of patients with mild to moderate VD. Methods: 30 VD patients were collected as the acupuncture group (AG) which was treated with "Sanjiao" acupuncture method once a day for six times a week and lasted for 12 weeks. 30 healthy elderly people were assigned to the normal group (NG) which had no treatment. The distribution of lymphocyte subsets and the levels of some inflammatory cytokines in peripheral blood of subjects were evaluated by the Flow Cytometry (FCM) and the Enzyme Linked Immunosorbent Assay (ELISA). Results: A total of 60 subjects were collected in this study while 58 subjects completed the entire trial. Before treatment, the levels of CD3+ T, CD4+ T cells, CD4+/CD8+, Tregs, B cells, IFN-γ and IL-10 of VD patients were significantly decreased compared with the normal group (all P<0.05 or P<0.01). The level of TNF-α in peripheral blood of VD patients was significantly increased (P<0.01). After acupuncture treatment, the levels of CD3+ T, CD4+ T cells and IFN-γ were significantly increased (all P<0.05 or P<0.01). The level of TNF-α was significantly decreased (P<0.01). The proportion of Tregs was increased (P<0.01), but it was still lower than that of the normal group (P<0.05). Conclusion: The acupuncture method can increase the proportion of CD3+, CD4+ T cells, and Tregs in peripheral blood of VD patients. And it reduces the levels of pro-inflammatory factor TNF-α which achieves the effect of anti-inflammatory and immuostimulation. It suggests that acupuncture can improve the peripheral immune dysfunction of the VD patients by regulating the distribution of lymphocyte subsets and the levels of inflammatory cytokines